Effects of Ulnar Collateral Ligament Reconstruction on Pitch Selection in Major League Baseball Pitchers. Issue 11 (16th November 2018) - Peterson, Eric E.; Handwork, Patrick; Soloff, Lonnie; Schickendantz, Mark S.; Frangiamore, Salvatore J.
Background: Ulnar collateral ligament (UCL) injuries represent one of the most common impairments to the throwing arm of professional pitchers. Return to play and postoperative performance metrics have been studied extensively, but pitch selection before and after surgery has not been evaluated. Purpose/Hypothesis: This study aimed to characterize the effects of UCL reconstruction on pitch selection in Major League Baseball (MLB) pitchers. We hypothesized that pitchers will throw fewer fastballs and a greater percentage of off-speed pitches after undergoing UCL reconstruction. Study Design: Retrospective cohort study; Level of evidence, 3. Methods: Using publicly available data, we evaluated MLB pitchers who underwent UCL reconstruction between 2003 and 2014. Pitching data were collected for the 2 seasons before UCL reconstruction as well as the first 2 seasons after reconstruction; the data consisted of the total number of pitches thrown and the percentage of fastballs, curveballs, changeups, and sliders. Repeated-measures analysis of variance was used with post hoc least significant difference pairwise t tests to evaluate for statistical significance at P < .05. Results: Overall, 87 pitchers (mean age, 28.2 ± 3.5 years) met all inclusion and exclusion criteria. There was a statistically significant difference in the total number of pitches thrown before and after surgery ( P < .01) as well as in the percentage of fastballs thrown before and after surgery ( P = .02). There was also a statistically significant increase in the use of curveballs between 1 and 2 years postoperatively (7.5% and 8.8%, respectively; P = .01). No other findings were statistically significant. Conclusion: Pitchers who underwent UCL reconstruction were shown to have a statistically significant decline in the percentage of fastballs thrown postoperatively as compared with before injury, with a compensatory trend toward an increased use of curveballs and sliders.